The book of two ways - Picoult, Jodi (Hodder & Stoughton, 2021)
Who would you be, if you hadn't turned out to be the person you are now? Dawn is a death doula, and spends her life helping people make the final transition peacefully. But when the plane she's on plummets, she finds herself thinking not of the perfect life she has, but the life she was forced to abandon fifteen years ago - when she left behind a career in Egyptology, and a man she loved. Against the odds, she survives, and the airline offers her a ticket to wherever she needs to get to - but the answer to that question suddenly seems uncertain. As the path of her life forks in two very different directions, Dawn must confront questions she's never truly asked: What does a well-lived life look like? What do we leave behind when we go? And do we make our choices, or do our choices make us? Two possible futures. One impossible choice.